2017
DOI: 10.1001/jama.2017.10569
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Ganciclovir on IL-6 Levels Among Cytomegalovirus-Seropositive Adults With Critical Illness

Abstract: The role of cytomegalovirus (CMV) reactivation in mediating adverse clinical outcomes in nonimmunosuppressed adults with critical illness is unknown.OBJECTIVE To determine whether ganciclovir prophylaxis reduces plasma interleukin 6 (IL-6) levels in CMV-seropositive adults who are critically ill. Double-blind, placebo-controlled, randomized clinical trial (conducted March 10, 2011-April 29, 2016 with a follow-up of 180 days (November 10, 2016) that included 160 CMV-seropositive adults with either sepsis or tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
113
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 107 publications
(118 citation statements)
references
References 28 publications
3
113
0
2
Order By: Relevance
“…Despite lower levels of CMV reactivation in the treatment group, no difference was noted in the primary outcome (IL-6 levels) although ventilator free days were higher in the treatment group [35]. In contrast, a single center trial of 124 CMV-seropositive patients undergoing mechanical ventilation randomized patients to receive anti-CMV prophylaxis with valacyclovir or low-dose valganciclovir.…”
Section: Should Antiviral Therapy Be Administered In the Context Of Vmentioning
confidence: 87%
“…Despite lower levels of CMV reactivation in the treatment group, no difference was noted in the primary outcome (IL-6 levels) although ventilator free days were higher in the treatment group [35]. In contrast, a single center trial of 124 CMV-seropositive patients undergoing mechanical ventilation randomized patients to receive anti-CMV prophylaxis with valacyclovir or low-dose valganciclovir.…”
Section: Should Antiviral Therapy Be Administered In the Context Of Vmentioning
confidence: 87%
“…In addition, interpretation in the current report is confounded by lack of concomitant T‐cell and innate immune function data. Recent studies of prophylactic antiviral drug therapy trials for prevention of CMV reactivation in immunocompetent humans have focused on safety and efficacy, and like most previously published observational trials largely ignore the contribution of underlying host immunity to reactivation resolution. Future trial designs should include such monitoring to enhance our understanding of how pre‐existing host immunity may contribute to the resolution of reactivation events.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, this treatment improved the T cells’ ability to kill tumour cells, accompanied by PD‐1 down‐regulation. A recent clinical study showed that ganciclovir treatment of CMV‐positive patients with sepsis does not affect serum IL‐6 levels while reducing the incidence of CMV reactivation, indicating that the drug does not have anti‐inflammatory effects . Although ganciclovir is not CMV‐specific, this observation prompts the discussion that many drugs used in clinical settings may have multiple functions and could therefore be repurposed for host‐directed therapy .…”
Section: Cmv‐specific Memory Inflation Shapes Global and Anti‐tumour mentioning
confidence: 99%